From nociception to pain perception, possible implications of astrocytes - Higinio-Rodríguez, Frida; Rivera-Villaseñor, Angélica; Calero-Vargas, Isnarhazni; López-Hidalgo, Mónica (Frontiers in Cellular Neuroscience, 2022)
Astrocytes are determinants for the functioning of the CNS. They respond to neuronal activity with calcium increases and can in turn modulate synaptic transmission, brain plasticity as well as cognitive processes. Astrocytes display sensory-evoked calcium responses in different brain structures related to the discriminative system of most sensory modalities. In particular, noxious stimulation evoked calcium responses in astrocytes in the spinal cord, the hippocampus and somatosensory cortex. However, it is not clear if astrocytes are involved in pain. Pain is a private, personal and complex experience that warns us about potential tissue damage. It is a perception that is not linearly associated with the amount of tissue damage or nociception, instead, it is constructed with sensory, cognitive, and affective components and depends on our previous experiences. However, it is not fully understood how pain is created from nociception. In this perspective article, we proposed that coherent activity of astrocytes in the spinal cord and pain-related brain areas could be important in binding sensory, affective and cognitive information on a slower time scale. We first give an overview of the mechanisms and neuronal networks that underlie the perception of pain and provide evidence to integrate the astrocytes in the construction of pain.